2022 23rd International Radar Symposium (IRS) 2022
DOI: 10.23919/irs54158.2022.9905068
|View full text |Cite
|
Sign up to set email alerts
|

A Compressive Sensing-Based Approach for Millimeter-Wave Imaging Compatible with Fourier-Based Image Reconstruction Techniques

Abstract: A compressive sensingbased approach for millimeter-wave imaging compatible with Fourier-based image reconstruction techniques. In Proceedings of the 23rd International Radar Symposium, IRS 2022 (pp. 87-91). (International Radar Symposium Proceedings).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In the literature, there are various techniques for image reconstruction [17][18][19]. It has been demonstrated that those techniques that offer a solution to the electromagnetic inverse scattering problem in the Fourier domain are much more computationally efficient than others [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are various techniques for image reconstruction [17][18][19]. It has been demonstrated that those techniques that offer a solution to the electromagnetic inverse scattering problem in the Fourier domain are much more computationally efficient than others [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Γ is designed in such a way that only one 1 is placed at random with a uniform distribution in each row and the rest of the entries are 0. Based on previous studies [3,29], for the dictionary matrix, the discrete Fourier transform (DFT) domain is considered. To perform CS reconstruction in (12), convex programming [30], or as an alternative, greedy algorithms [31] can be used.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The most basic way to create a two-dimensional (2D) active radar aperture is to use a transmitter-receiver (Tx-Rx) antenna pair in monostatic mode and capture the scene information through a mechanical raster scan [7,8]. However, despite its simplicity, such a mechanism is not efficient in terms of the data acquisition rate.…”
Section: Introductionmentioning
confidence: 99%